Chandabaji versus entrepreneurship : economic liberalisation and youth force in Bangladesh - Khan, Shahedul Anam; Afroze, Shaheen (Academic Press and Publishers Ltd., in collaboration with Bangladesh Institute of International and Strategic Studies, 1999)
Papers presented at the 3rd BIISS Young Scholar's Seminar held in September, 1998, at Bangladesh Institute of International and Strategic Studies.